Associations among appetite, social networks, and loneliness in community-dwelling older adults: A cross-sectional study - Keisuke Fujii, OTR, PhD; Kento Noritake, MS; Daiki Nakashima, MS; Yuta Kubo, PhD; Kyosuke Yorozuya, PhD; Soma Tsujishita, PhD; Naoki Tomiyama, MS (Archives of Gerontology and Geriatrics Plus)
Purpose: This study aimed to clarify the association between reduced appetite and social factors, particularly social networks and loneliness, among community-dwelling older adults. Appetite is a key determinant of nutritional status and overall health in older adults, and its decline has been linked to adverse health outcomes, including frailty, sarcopenia, and increased mortality. Methods: Primary assessments included the Japanese version of the Simplified Nutritional Appetite Questionnaire, Lubben Social Network Scale-6, and UCLA Loneliness Scale to evaluate appetite, social networks, and loneliness. Multiple regression analysis was performed with appetite as the dependent variable and social network and loneliness as independent variables. Results: Loneliness was significantly associated with reduced appetite in 126 participants, whereas social network size had no significant relationship with appetite. Conclusions: These findings suggest that in the context of reduced appetite among older adults, subjective loneliness may be a more critical factor than the mere quantity of social contact. The results of this study indicated that reducing loneliness is crucial when considering intervention strategies to improve appetite in older adults. In addition to traditional population-based approaches aimed at expanding social networks, individualized interventions that address loneliness and provide psychological support may be necessary.